Preparation and Characterization of Chinese Leek Extract Incorporated Cellulose Composite Films - Zeng, Qiying; Xiao, Naiyu; Zhang, Xueqin; Luo, Wenhan; Xiao, Gengshen; Zhai, Wanjing; Zhong, Le; Lan, Bifeng (Frontiers in Bioengineering and Biotechnology, 2021)
This study aimed to prepare microcrystalline cellulose (MCC) films with good mechanical properties via plasticization using Chinese leek (CL, Allium tuberosum) extract. The microstructural, crystal structure, mechanical properties, barrier ability, and thermal properties of the films were investigated. The chemical structure analysis of CL extract showed the existence of cellulose, lignin, and low molecular weight substances, such as polysaccharides, pectins, and waxes, which could be acted as a plasticizer to enhance the properties of MCC:CL biocomposite films. Results of scanning electron microscopy (SEM) and atomic force microscopy (AFM) analyses indicated the good compatibility between MCC and CL extract. When the volume ratio of the MCC:CL was 7:3, the MCC:CL biocomposite film exhibited the best comprehensive performance in terms of water vapor permeability (2.11×10-10 g/m·s·Pa), elongation at break (13.2 ± 1.8%), and tensile strength (24.7 ± 2.5 MPa). The results of a UV absorption analysis demonstrated that the addition of CL extract improved the UV-shielding performance of the films. Therefore, this work not only proposes a facile method to prepare MCC films with excellent mechanical properties via plasticization using CL extract but also broadens the potential applications of MCC films in packaging area.